CaCO3–Polymer Nanocomposite Prepared with Supercritical CO2. (1st August 2018) - Wakayama, Hiroaki
Abstract : A novel process for generation of a CaCO3 –polymer nanocomposite with a controlled three-dimensional shape was developed. Specifically, a nanocomposite with a high CaCO3 content was produced by introducing supercritical CO2 into a polymer matrix containing Ca ions. A mixture of poly(vinyl alcohol), Ca acetate, and poly(acrylic acid) was poured into a mold, the mold was placed in an autoclave, and CO2 was introduced to precipitate CaCO3 within the polymer matrix. Laser Raman spectroscopy and transmission electron microscopy showed that this process produced a nanocomposite containing highly dispersed CaCO3 (aragonite) nanoparticles. The flexural strength of the nanocomposite was larger than the flexural strengths of limestone and CaCO3 produced by hydrothermal hot pressing. The use of supercritical CO2 facilitated CO2 dissolution, which resulted in rapid precipitation of CaCO3 in the polymer matrix. The above-described process has potential utility for fixation of CO2 .